Ali Rustam vs. Muhyiddin - Raihan Suleiman Palestin (Kuala Lumpur : Diterbitkan dan dicetak oleh Prismatic Printing Services, 2009)
Issues on politics and leadership in Malaysia.
In Malay.
Keywords: Mohd. Ali Rustam, -- Datuk Seri, -- 1949-; Muhyiddin bin Haji Mohd. Yassin, -- Tan Sri Dato' Haji; United Malays National Organisation; Malays (Asian people) -- Political activity -- Malaysia